Tectona grandis Linn. challenges and perspectives of the potential use of the species: Agroindustria - Lazo-Pérez, Yamila (2024)
Tectona grandis Linn f. is a species belonging to the Lamiaceae family, which grows in the Indian peninsula, Myanmar, Thailand, Lao People’s Democratic Republic. The present study offers a pharmacognostic evaluation (numerical indices) and evaluates the antioxidant power of the aqueous extract of the leaves of T. grandis. A drying study was carried out in the sun and in an oven to determine the most suitable method, and the oven method turned out to be the most appropriate, with a maximum drying time of 30 h. The numerical indices of residual moisture, total ash, water-soluble ash and hydrochloric acid-insoluble ash were used to guarantee the quality of the plant material and establish, for the first time, these parameters for the leaves of the species. The content of total phenols was determined, with values between 75 and 310 mg GAE·gDE-1, as well as the evaluation of the reducing potential of the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), and the antioxidant activity of the extract by the system β-carotene/linolenic acid. The extract obtained from T. grandis leaves showed promising antioxidant activity.